Diagnostic Radiation Exposure in Patients with Inflammatory Bowel Disease - Catherine Langevin; Lysanne Normandeau; Mickael Bouin (Canadian Journal of Gastroenterology and Hepatology)
Background. Because of the chronic and relapsing nature of inflammatory bowel disease (IBD), which often requires characterization with CT scan, IBD patients might be exposed to a large amount of radiation. As a cumulative effective dose (CED) ≥ 100 mSv is considered significant for stochastic risks of cancer, it is important to monitor and control the radiation exposure of the IBD patients. In the present work, we aimed to quantify the mean CED in IBD patients to assess any harmful effects of radiation. Methods. This study includes 200 IBD patients, identified retrospectively, from the outpatient clinics of the Centre Hospitalier de l’Université de Montréal between January 1, 2010, and February 15, 2017, from the gastroenterologists’ patients lists. The number and type of each radiology test performed were listed for each patient during the study period and the CED was calculated using our institution’s dose index when available and standardized tables. Results. Among the 200 IBD patients, 157 patients had Crohn’s disease (CD), 41 had ulcerative colitis (UC), and 2 had indeterminate colitis. The mean CED for IBD patients was 23.1 ± 45.2 mSv during a mean follow-up duration of 4.3 years. CED was higher among patients with CD than with UC (27.5 ± 49.5 versus 6.8 ± 14.8 mSv; p<0.01). Six patients were exposed to a high CED (>100 mSv) and all had CD. Conclusion. While potentially harmful levels of radiation exposure are of concern in only a small number of patients, strategies to limit such exposure are encouraged when clinically appropriate.